Integrals of operator-valued functions - Raimond A. Struble (International Journal of Mathematics and Mathematical Sciences)
Mikusinski-type expansions of operator-valued functions are discussed in some detail. As a natural part of the development, a kernel concept for operators is proposed and an elaborate system of convolution quotients in one and two variables is obtained.